Current status and development trends in CKD with frailty research from 2000 to 2021: a bibliometric analysis - Guowei Yuan; Yaqin Yang; Yujie Lin; Jiarong Lin; Yuchi Wu (Renal Failure)
Introduction The prevalence of chronic kidney disease (CKD) is gradually increasing in the elderly population. At the same time, frailty has become one of the research hotspots in the field of geriatrics. Bibliometric analyses help to understand the direction of a field. Therefore, this study aimed to analyze the status and emerging trends of frailty in CKD patients.Data and methods The Web of Science Core Collection (WoSCC) database was screened for relevant literature published between 1 January 2000 and 31 December 2021. Next, publications were analyzed for information including authors, journals, cited references, citing journals, institutions, countries and regions, high-frequency keywords and co-citations using VOSviewer, Microsoft Excel, and R software.Results A total of 2223 articles were obtained, from which 613 relevant articles were selected based on title and abstract screening. There was an upward trend in the number of annual publications and Johansen KL was considered the most contributing author in the field. The Clinical Journal of the American Society of Nephrology was the most productive research journal. Johns Hopkins University is the most published organization. The United States is the global leader in the field and contributes the most to research. Research hotspots focus on epidemiological studies of frailty and frailty intervention.Conclusions This study presents a comprehensive bibliometric analysis of CKD and frailty research. Key findings highlight the current focus on early screening and assessment of frailty in CKD patients, as well as physical function interventions in frail patients.